Puberty: Normal physiology (brief overview). Issue 3 (June 2019) - Wood, Claire L.; Lane, Laura C.; Cheetham, Tim
Abstract : Puberty is a defining phase of human development where growth ends and the ability to reproduce begins. An understanding of the events leading up to puberty highlights the fact that this is the culmination of a process of skeletal and gonadal activity that has been ongoing since conception. Although there is natural variation in the timing of events in and around puberty the basic underlying processes are common to all healthy human beings. This chapter is intended to outline the mechanisms underlying normal growth and development before and during puberty. By understanding normality the pathological processes that give rise to abnormalities of pubertal development can be understood more easily.